Evidence for a DC-specific inhibitory mechanism that depends on MyD88 and SIGIRR. - Drexler, S; Wales, J; Andreakos, E; Kong, P; Davis, A; Garlanda, C; Mantovani, A; Hussell, T; Feldmann, M; Foxwell, B (2010)
Dendritic cells (DC) are an essential link between the innate and adaptive immune response. To become effective antigen-presenting cells DC need to undergo maturation, during which they up-regulate co-stimulatory molecules and produce cytokines. There is great interest in utilizing DC in vaccination regimes. Over recent years, Toll-like receptor (TLR) signalling has been recognized to be one of the major inducers of DC maturation. This study describes a mutant version of the TLR adaptor molecule MyD88 (termed MyD88lpr) as a novel adjuvant for vaccination regimes. MyD88lpr specifically activates DC by disrupting a DC intrinsic inhibitory mechanism, which is dependent on single immunoglobulin IL-1R-related. Moreover, MyD88lpr was able to induce an IgG2a-dominated response to a co-expressed antigen, suggesting Th1 immunity. However, when used as a vaccine adjuvant for Influenza nucleoprotein there was no significant difference in the lung viral titres during the infection. This study describes MyD88lpr as a potential adjuvant for vaccinations, which would be able to target DC specifically.